Perbandingan Efektivitas Kompres Daun Kemangi dan Minyak Oles Herbal Terhadap Derajat Puting Lecet - silvia ananda; Agrina; Yesi Hasneli. N (HEALTH CARE : JURNAL KESEHATAN, 2022)
Introduction: Cracked nipples are a condition of trauma to the nipple in the form of sores or cracks. Sores on the nipples can lead to serious complications if not properly intervened. Purpose: To determine the effectiveness of basil leaf compresses and herbal topical oil on the degree of cracked nipples of breastfeeding mothers. Methodology: This study used a quantitative research method, with a quasi-experimental research design with two pre-test-post-test groups without a control group. The sample for this study who were breastfeeding mothers with grade 2 cracked nipples which were divided into 25 people in the experimental group 1 (basil compresses) and 25 people in the experimental group 2 (herbal topical oil). Respondents were intervened for 7 days according to the inclusion criteria using a purposive sampling technique. The analysis used was univariate and bivariate analysis using the Wilcoxon test and the Mann Whitney test. Results: Comparison of the effectiveness of basil leaf compresses and application of herbal oil using the Mann Whitney test with p value (0,317), or p > α (0,05). Conclusion: Both interventions were equally effective in reducing the degree of cracked nipples, but based on statistic there was no difference in the effectiveness of basil leaf compresses and applying herbal oil on the degree of cracked nipples of breastfeeding mothers.